GAMIFICATION AS A CATALYST FOR BRAND ENGAGEMENT AMONG YOUTHS IN SOUTHEAST NIGERIA: A SOCIO-CULTURAL PERSPECTIVE ON STRATEGIC MARKETING OUTCOMES (UNIZIK Journal of Marketing, 2025)
In today’s digitally driven marketplace, gamification has emerged as a powerful tool for enhancing consumer engagement. The purpose of this study is to examine how gamification acts as a catalyst for brand engagement among youths in Southeast Nigeria, exploring the sociocultural factors that influence strategic marketing outcomes. Grounded in consumer engagement theory, the research adopts a mixed-method approach, utilising simple random sampling to survey 380 Indomie Noodles consumers aged 18–35 across five Southeastern Nigerian states, complemented by in-depth interviews with marketing professionals. Findings reveal that sociocultural factors—particularly peer influence, collectivism, and traditional values—play a pivotal role in shaping the effectiveness of gamified marketing. Notably, family orientation exhibited a negative yet significant impact, indicating potential resistance to gamification among familycentric individuals. Among various gamification elements, rewards, leaderboards, and progress tracking significantly enhanced brand engagement, while competitions, badges, and challenges showed no notable effect. The study recommends that marketers align gamification strategies with cultural values, emphasizing communal motivators over individualistic or competitive features. Prioritizing tangible incentives and progress-based elements is essential for sustaining user interaction and maximizing brand loyalty.
Keywords: Gamification, Brand Engagement, Youths, Socio-Cultural, Strategic Marketing.